MANDIBULAR BONE EROSION ASSOCIATED WITH HYALURONIC ACID FILLER: CBCT CASE REPORT - Moreira, José Roberto Alves; Brandão, Henrique Barcelos; Bagatini, Ana Thais; Pitta, Marcos Cesar; Gandini Junior, Luiz Gonzaga; Pinto, Ary dos Santos (Seven Editora, 2026)
We report a case of bone erosion in the mental region associated with hyaluronic acid (HA) injection for cosmetic purposes, incidentally identified in a patient undergoing orthodontic treatment with miniscrew-assisted rapid palatal expansion (MARPE). This case offers rare sequential radiographic documentation using cone-beam computed tomography (CBCT) both before and after HA injection, along with intraoperative confirmation of the lesion. These findings provide further support for the hypothesis of HA-induced bone resorption. This report underscores the critical role of imaging in interdisciplinary clinical practice and contributes meaningful evidence regarding the potential adverse effects of facial fillers on underlying osseous structures.DOI: https://doi.org/10.56238/sevened2026.008-021